Violence in Querétaro, a bird's eye view (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
Violence is, unfortunately, a constant in history and as such, possible to be recorded. Others before me have already started that path, showing that, despite the supposed advances of civilization, barbarism persists in various ways, one of them through daily violence. In this work, we account for the multiple forms of violence that is experienced, on a daily basis, in Querétaro (Mexico), as well as the mechanisms through which this violence is reproduced, in a normalized way, although not so invisible. It is proposed that the increase in violence, and especially against women, is in part the result of a cultural construction of relationships between men and women, in its multiple dimensions, that runs through Mexican culture.
Keywords: violence; women; daily life; Querétaro (Mexico); culture